WORKSHOP PENGELOLAAN HAK KEKAYAAN INTELEKTUAL BAGI GURU SMK MUHAMMADIYAH KARTASURA - Susilo, Dahlan; Hasana, Henny Tri Hastuti; Ernawati, Sri (Awatara Publisher, 2024)
Intellectual Property Rights (IPRs) management is an important aspect in maintaining creativity and innovation in the world of education. In order to improve teachers' understanding and skills regarding IPRs, workshop activities have been held at SMK Muhammadiyah Kartasura. This activity aims to provide insight to teachers regarding the importance of IPRs and how to register and manage intellectual property rights in the world of education. Through this workshop, it is hoped that teachers can understand the legal aspects of IPRs and be able to protect the works and innovations that have been produced can be properly documented and legally protected.